Effectiveness of Liquid Smoke Concentration of Red Fruit Seed Waste as A Bioherbicide on the Physiology and Yield of Moai Upland Rice by Intercropping with Black Soybeans in Jayawijaya District - Mahanani, Anti Uni; Purwanto, Edi; Haryanto, Totok Agung Dwi; Rahayu, Muji (Journal of Ecohumanism, 2025)
Bioherbicide from red fruit seed waste and contains phenolic compounds. The objective are: 1) to analyze the effectiveness of red fruit seed waste on the physiology and yield of Moai upland rice; 2) to analyze which concentration of red fruit seed waste liquid smoke is most effective on the physiology and yield of Moai upland rice plants. The design used in this research was a Complete Randomized Block Design with two treatment factors, namely two factors intercropping Moai with black soybeans (T1), Moai rice monoculture (T2), and the second factor is: a) Concentration of 0 ml liquid smoke/l water (S0); b) Concentration of 200 ml liquid smoke/l water (S1); c) Concentration of 250 ml liquid smoke/l water (S2); d) Concentration of 300 ml liquid smoke/1 water (S3). Conclusion: 1) Liquid smoke from red fruit seed waste is effective on the net assimilation rate and growth rate of Moai; number of panicles, dry weight of 100 seeds, number of hollow seeds and number of pithy seeds of Moai; harvest index and chlorophyll content of Moai; 2) The most effective concentration of red fruit seed waste liquid smoke on the physiology and yield of Moai plants is the concentration of red fruit seed waste liquid smoke of 250 ml liquid smoke/l water (S2).